Counterpoint unravelled - De Bonis, Maurício [UNESP] (OPUS, 2018)
The diversity of pedagogical proposals and solutions grouped around what has come to be called counterpoint in music education does not eliminate a common issue shared by most: the lack of clarity of a well-defined reference system compromises its effectiveness. Defining a referential repertoire is not always sufficient to remedy this incongruity, since many of the most common pedagogical strategies are diametrically incompatible with the musical thought of an era. It is necessary to critically review the most commonly used treatises in light of their precision of the approach of the musical systems employed; of each referential specificity within the modal and tonal systems. Likewise, the teaching approach by species calls for a critical reappraisal, as do the treatises that do not employ this methodology. At this point we bring forth a concept proposed by Arnold Schoenberg to distinguish homophonic thinking and polyphonic thinking in tonal music as we expand it in order to reveal considerations on the specificity of melodic and contrapuntal thinking in modal music. It is thus possible to base a critical discussion on what would be the functions and effectiveness of a pedagogical proposal of this order in music training today.
Por um desemaranhamento do contraponto
Keywords: Counterpoint; Melody; Musical structure; Polyphony